Improving Student Performance and Personal Growth: A Review of Group Counseling in High Schools - Asadi, Ali Reza; Mede , Enisa (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The high school years are a critical period in students’ lives, marked by rapid academic, social, and emotional development. Group counseling in high schools has emerged as a vital tool to support students through these challenges, offering a unique avenue for addressing a range of developmental and educational needs. This article aims to explore the impact of group counseling on enhancing student performance and personal growth within high school settings. Methods and Materials: The review involved a comprehensive search of academic databases using keywords such as "group counseling," "high school," "student performance," and "personal growth." Studies specifically examining the impact of group counseling on high school students were included. The selected literature was analyzed and synthesized to provide a coherent understanding of the current state of group counseling in high schools, focusing on its methods, effectiveness, challenges, and best practices. Findings: The review highlights the effectiveness of group counseling in various domains, including academic support, social skills enhancement, and mental health improvement. Key challenges in implementing group counseling programs were identified, such as resource constraints, student participation, and variability in program implementation. Effective practices and recommendations for schools were outlined, including tailored interventions, collaborative approaches, continuous training for counselors, and integrating counseling into the school curriculum. Conclusion: Group counseling in high schools is a valuable intervention that significantly impacts student performance and personal growth. It addresses the holistic needs of high school students, contributing to their overall success and well-being. The review suggests areas for future research and development in group counseling and recommends that schools develop policies and practices to integrate group counseling into their educational framework, ensuring that all students have access to these vital services.